MODEL GAYABERAT 2D UNTUK MENGUNGKAP STRUKTUR GEOLOGI BAWAH PERMUKAAN PADA DAERAH PANAS BUMI NATAR: 2D CONCEPTUAL MODEL ON NATAR GEOTHERMAL SYSTEM BASED ON GRAVITY DATA - Juliarka , Bella Restu; Iqbal, Mochamad (Buletin Sumber Daya Geologi, 2020)
The Natar geothermal field is located in Natar District, which is approximately 10 km north of Bandar Lampung, Lampung Province. This geothermal area is unique because the manifestation of hot springs that appear on the surface is in a relatively flat area. Geological observations on outcrops to determine the geological structure that control the hot springs are difficult to carry out due to limited rock outcrops, so geophysical methods are needed to interpret subsurface conditions such as gravity methods. The geology of the study area is covered by Lampung Formation consists of pyroclastic - volcaniclastic rocks with thickness reaching 200 m. The result of gravity data processing shows the value of Bouguer anomaly which ranges from 51.0 to 62.6 mGal. The interpretation of Bouguer's anomaly data shows five fault structures predominate northwest-southeast and north-south trend, which act as the water path discharge. This trend indicates that the geological structure in the study area is still related to the Great Sumatran Fault, which is also trending northwest-southeast. The 2D subsurface modeling is conducted by using Oasis Montaj software 8.4 produces three layers of rock density, namely a layer associated to the Lampung Formation with density of 1.9 g / cm3, and two layer basements with densities of 2.54 g / cm3 and 2.76 g / cm3 respectively, forming horst and graben like structures in the study area. Exploration drilling for further research is recommended to the west of the hot springs to confirm the subsurface model.